First in class monoclonal antibody potentiating human follicle stimulating hormone activity improves spermatogenesis in azoospermic rodent models - Kara, Elodie; Decourtye, Jérémy; Dupuy, Laurence; Casteret, Sophie; Bouchard, Philippe; Frydman, René; Maurel, Marie-Christine (Frontiers in Endocrinology, 2025)
IntroductionIn vitro and in vivo in rodent models were used to study the effects of a human follicle-stimulating hormone (hFSH)-potentiating monoclonal antibody (IGX12) on hFSH bioactivity.MethodsPotentiation of recombinant hFSH (rhFSH)-, human luteinizing hormone/chorionic gonadotropin (hLH/hCG)-, or human thyroid stimulating hormone (TSH)-mediated cyclic adenosine monophosphate (cAMP) induction in vitro was performed using HEK 293 cells overexpressing either human FSH receptor (hFSH-R), human LH-receptor (hLH-R) or human thyroid stimulating hormone receptor (hTSH-R). The effect of rhFSH on ovarian weight and hCG on seminal vesicle weight was tested in immature female or male rats. Potentiation of spermatogenesis was examined in adult male rats with acquired azoospermia and hpg mice homozygotic for the hypogonadal mutation (Gnrh1hpg).ResultsIGX12 dose-dependently potentiated rhFSH induction of cAMP production in vitro with an approximately 30% larger maximum response and increased ovarian weight by 1.8 fold in vivo versus rhFSH alone. A higher concentration of IGX12 (200 μg/ml) demonstrated a slight potentiating effect on hLH or hCG in vitro and non-statistically significantly increased seminal vesicle weight by 1.3 fold in vivo. No potentiating effect of IGX12 on hTSH was observed. In vivo, the addition of IGX12 to exogenous gonadotropins in the rat acquired azoospermia model increased testes weight by 1.8 fold and sperm counts by 1.5 fold compared with gonadotropins alone and was more effective than doubling the gonadotropin dose. In the mouse congenital azoospermia model, versus gonadotropins alone, addition of IGX12 significantly improved sperm counts in the testes by 3.5 fold and in the epididymides by 5.5 fold.ConclusionIGX12 is a first-in-class humanized monoclonal antibody (mAb) that potentiated FSH activity in vitro and stimulated spermatogenesis more effectively than gonadotropins alone in congenital and acquired azoospermia rodent models, even when increasing the dose of gonadotropins had no additional effect. These in vitro and in vivo findings suggest that IGX12 could have promise as a future treatment option for men with azoospermia and oligozoospermia.